A novel inflammation-related lncRNAs prognostic signature identifies LINC00346 in promoting proliferation, migration, and immune infiltration of glioma - Zeng, Wen-Jing; Zhang, Lei; Cao, Hui; Li, Dongjie; Zhang, Hao; Xia, Zhiwei; Peng, Renjun (Frontiers in Immunology, 2022)
In this study, GBM and LGG patients' data were obtained from TCGA and CCGA dataset. A total of 13 inflammation-related lncRNAs with a high prognostic value were identified using univariate cox regression analysis, multivariate cox regression analysis, and Lasso analysis. The LINC00346, which is one of the 13 lncRNAs identified, was positively associated with type 2 macrophage activation and the grade of glioma. FISH and immunohistochemical staining showed that LINC00346 was highly expressed in high-grade glioma, while type 2 macrophages key transcription factor STAT3 and surface marker CD204 were highly expressed simultaneously. LINC00346 high expression group could be more sensitive to the anti–PD-1 and anti-CTLA-4 therapy. LINC00346 was also associated with tumor proliferation and tumor migration validated by EdU assay, cell colony assay, CCK8 assay, and transwell assay. These findings reveal novel biomarkers for predicting the prognosis of glioma and provides an overview of the relationship between lncRNAs, inflammation, and glioma and possible immune checkpoint target for glioma.